Pengaruh Locus of Control dan Gaya Hidup Konsumerisme terhadap Intention to Buy pada Mahasiswa Fakultas Ekonomi Unusida - M. David Amirulloh; Amin Al Kholidi; Adinda Bahar; Siti Nurul Wahidah (Journal of Management and Creative Business, 2024)
This study aims to analyze the influence of locus of control and consumerist lifestyle on intention to buy among UNUSIDA Faculty of Economics students. The population in this study is all UNUSIDA Faculty of Economics students class of 2021. The sample will be randomly selected from this population. The number of samples taken was 15 people, which was sufficient for multiple linear regression analysis. Data collection was carried out through distributing questionnaires which included scales measuring locus of control, consumer lifestyle and intention to buy. The data analysis technique used is multiple linear regression. The results of this study show that both Locus of Control and consumerism lifestyle have a significant positive influence on intention to buy among students. Even though the interaction between these two variables is not significant, the results of this research still provide valuable insights for more effective marketing strategies and education policies. Strengthening internal LOC and understanding the consumerist lifestyle can help students make wiser and more responsible purchasing decisions. This research will also provide valuable insights for marketing practitioners and business strategy planners. This research is expected to make a significant contribution both in the development of academic theory and in business and marketing practice. By better understanding student consumer behavior, we can create a healthier and more sustainable environment for the development of individuals and society as a whole.